Woman as Second-Class Citizens: The Impact of Patriarchy on Afghan Women in Hashimi’s One Half from The East - Amani, Zaenab; Samar, Rubina; Salumahale, Fahad Esmaeili (Cultural Narratives, 2024)
Nadia Hashimi's novel, One Half from The East, serves as a lens to explore the pervasive issue of gender inequality in a patriarchal society. This study analyzes the depiction of women, who are consistently viewed as inferior to men and denied fundamental rights. Employing qualitative research methods and Bell Hooks' feminist theory, the analysis exposes the limitations placed upon women within this social structure. The research highlights how Afghan women, like Obayda and Rahima who resort to disguising themselves as men, face oppression and discrimination from birth. Their restricted access to education, healthcare, and even control over their own bodies exemplifies the profound impact of patriarchy on their lives. The findings of this study suggest that gender inequality is deeply ingrained in patriarchal societies and continues to limit the rights and freedoms of women. This study underscores the ongoing struggle for women's equality not just in Afghanistan, but across the globe. In conclusion, this novel became an evident that the fight for women's equality is far from over, and efforts must be made to challenge and dismantle patriarchal structures not just in Afghanistan, but worldwide.